PENGARUH BELANJA PEMERINTAH PUSAT DAN NILAI TUKAR TERHADAP INFLASI DI KOTA TERNATE - Tesapati, Satria (Buletin Studi Ekonomi, 2023)
This study was conducted with the aim of photographing the effect of central government spending and the exchange rate of the Rupiah against the US Dollar for the period January 2016 to 2022. This study uses the VECM method to determine the long-term and short-term relationship of these variables, to see the response of inflation to spending shocks and exchange rates. and the contribution of each variable. The result of this research is that in the long term only the variable of goods expenditure has a significant effect on inflation. Meanwhile, in the short term, personnel expenditures, goods expenditures and exchange rates have a significant effect on Ternate City Inflation. Inflation's response to shocks in personnel spending and exchange rates was relatively small and short-lived. However, Inflation responds to a relatively large and long-lasting shock in goods spending. If sorted from largest, the contribution of each variable to the movement of inflation is expenditure on goods, exchange rates and then personnel expenditure. The implication of this research is that stakeholders in Ternate City need to pay attention to the surge in personnel expenditure, goods expenditure and exchange rate fluctuations